organizational authority in the Algerian public institution; Histography of the path and workers’ representations - bentahar , hamza (Journal of Social Sciences and Humanities, 2025)
Based on the principle of the hierarchy of power within organizations around which all organizational processes revolve, and in accordance with the propositions of the emergence and fragmentation of power among the various components of the organization and its levels and its instability at one organizational level rather than another, organizational power has become an attractive subject for organizational and administrative studies that has attracted - and continues to attract - researchers and theorists since the emergence of these organizations in their early beginnings.The research paper is a theoretical study that attempts to trace the locations of organizational power within the Algerian institution since independence, and the mechanism of its formation and distribution among the various components of the organization (the formal authority of the administration and the legal authority of the syndicate and the informal authority), which concluded with several results related to the composition of the organizational power of the Algerian institution in the stages of economic change that the country witnessed from the stage of self-management to the stages of privatization